Plan estratégico de desarrollo institucional para la “la liga deportiva cantonal de La Maná”, provincia de Cotopaxi periodo (2012-2016) - Valencia Armas, Edgar Froilán (2014)
The present investigation refers to the design of a Institutional Development Strategic Plan for La Maná Cantonal Sports League Cotopaxi Province, period 2012 – 2016, with the purpose of improving the different activities and their competitiveness in their sports disciplines, the detail of the theory with topics related to the present project, then it is presented the survey directed to the directives, employees, coaches, monitors and athletes of the institution with their corresponding analysis, also it is included the objectives and the description of the proposal, afterward, it is possible to see the situational analysis.